2016
DOI: 10.1155/2016/1368481
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles Improve the Diclofenac Availability in Vitreous after Intraocular Injection

Abstract: Purpose. In order to improve the drug availability after intravitreal administration, solid lipid nanoparticles (SLNs) containing diclofenac were prepared. Methods. In this experimental study, 18 albino rabbits were included. In right and left eyes of all rabbits, SLNs containing diclofenac and commercial form of diclofenac (0.3 mg drug) were intravitreally injected, respectively. One, four, twelve, twenty-four, and forty-eight hours after injection, vitreous and aqueous humor samples were obtained in all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Biodegradable implants [75], non-biodegradable implants [76], biodegradable microspheres [71], nanoparticles [77], dendrimers [78], and hydrogels [79] have been used for intravitreal drug administration. Moreover, some sophisticated systems have been developed for the treatment of chronic and refractory ocular diseases, such as a microelectromechanical systems (MicroPump) [80] and a port delivery systems (PDS) [81].…”
Section: Posterior Routementioning
confidence: 99%
“…Biodegradable implants [75], non-biodegradable implants [76], biodegradable microspheres [71], nanoparticles [77], dendrimers [78], and hydrogels [79] have been used for intravitreal drug administration. Moreover, some sophisticated systems have been developed for the treatment of chronic and refractory ocular diseases, such as a microelectromechanical systems (MicroPump) [80] and a port delivery systems (PDS) [81].…”
Section: Posterior Routementioning
confidence: 99%
“…The purpose of proposing drug-loaded SLNs is to overcome the drawbacks associated with other colloidal carriers, such as liposomes. Indeed, compared to liposomes, SLNs have numerous advantages, including an easy and economical preparation without the use of organic solvents [ 84 , 86 , 87 ]. SLNs consist of solid fats (in the range 0.1–30% by weight) dispersed in an aqueous phase.…”
Section: Methods Of Loading Active Principles Into Contact Lensesmentioning
confidence: 99%
“…These nanocarriers can encapsulate micromolecules, siRNA, DNA, and proteins. Abrishami et al injected solid lipid nanoparticle-conjugated diclofenac intravitreally and found that mild improvement in drug efficacy occurred in the intraocular space [ 102 ]. After sunitinib-encapsulated solid lipid nanoparticles were administered intravitreally into rabbit eyes, drug efficacy was enhanced [ 103 ].…”
Section: Efforts To Enhance the Intraocular Pharmacokinetics And Pmentioning
confidence: 99%